2022
DOI: 10.2176/jns-nmc.2021-0384
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Cranial Morphology Based on Three-dimensional Scan Analysis in 1-month-old Healthy Infants in Japan

Abstract: Currently, molded helmet therapy is used to treat infants with deformational plagiocephaly. However, the indices of normal cranial shape remain unclear, and thus, the prevalence of deformational plagiocephaly is unknown, particularly in Japan. We investigated the reference values for cranial morphological characteristics in 1-month-old Japanese infants using a three-dimensional scanner, to determine the prevalence of deformational plagiocephaly. One hundred fifty-three healthy infants who visited three hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…As shown in our measurement precision analyses, the 3D scanner used in our current study was useful for considering human errors between measurers in 2D evaluations [ 7 , 8 ]. Normal reference values of the measurement variables obtained by the 3D scanner in 1-month-old healthy Japanese male or female infants were shown in our recently published report [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our measurement precision analyses, the 3D scanner used in our current study was useful for considering human errors between measurers in 2D evaluations [ 7 , 8 ]. Normal reference values of the measurement variables obtained by the 3D scanner in 1-month-old healthy Japanese male or female infants were shown in our recently published report [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 19 ) According to these criteria, most infants in Japanese studies, including this present study, were considered hyperbrachycephalic. 11 , 17 , 20 ) Koizumi et al suggested the following standards for classifying CI in Japanese infants: mesocephaly, 79.2%-93.8%; brachycephaly, 93.9%-101.1%; and hyperbrachycephaly, 101.2% or more. 20 ) Based on these standards for Japanese infants, the infants in this study met the standards for mesocephaly.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, we found that the incidence of DP is high among Japanese infants, with approximately 5% of healthy infants requiring helmet therapy. 10 , 11 ) Concerns that the number of infants requiring cranial correction will increase in the future and that the limited availability of 3D scanners will delay accurate diagnosis have already been raised. Early registration of handheld 3D scanners as medical devices is therefore desirable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations